Asthma and obesity increase inflammatory markers in children - Shailesh, Harshita; Noor, Safa; Hayati, Lena; Belavendra, Antonisamy; Van Panhuys, Nicholas; Abou-Samra, Abdul Badi; Worgall, Stefan; Janahi, Ibrahim (Frontiers in Allergy, 2025)
BackgroundAsthma and obesity are both characterized by inflammation. However, the combined impact of these conditions on inflammatory mechanisms in children has not been studied extensively. To address this gap, we investigated the interaction effects of asthma and obesity on inflammation in children.MethodsThe multiplex and singleplex assays were used to measure the levels of circulating cytokines, including IL-2, IL-5, IL-10, IL-13, IL-17A, IL-22, IL-33, IFN-γ, TNF-α, and the adipokine leptin, in plasma. The study included 97 children with normal weight and asthma (NW-A), 100 children with overweight/obesity and asthma (OO-A), 100 with overweight/obesity and no asthma (OO), and 67 normal weight children and no asthma (NW). The independent effects of asthma, obesity, and their interaction effect on these inflammatory markers were assessed using multiple regression analysis.ResultsAsthma was associated with the increased expression of pro-inflammatory cytokines, including IL-2, IL-5, IL-13, IL-17A, IL-22, IL-33, and TNF-α, and reduced levels of anti-inflammatory cytokine, IL-10 and adipokine, leptin in the circulation. Overweight/obesity was also linked to increased plasma levels of IL-5, IL-17A, IL-22, IL-33, TNF-α, and leptin and decreased levels of IL-10. In addition, obesity and asthma showed a significant interaction effect on the plasma levels of IL-5, IL-10, IL-17A, IL-33, TNF-α, and leptin. However, the interaction did not result in a synergistic or additive impact on cytokines, indicating a moderating effect of obesity on inflammation in pediatric asthma.ConclusionBoth asthma and overweight/obesity were independently associated with increased expression of pro-inflammatory cytokines and decreased expression of anti-inflammatory cytokine in children. While the concurrent presence of asthma and obesity altered the inflammatory profile, it did not synergistically amplify the inflammation. These findings challenge the previous view that obesity enhances inflammation in individuals with asthma and highlight the importance of considering both conditions while treating obesity-associated asthma in children. Future studies are necessary to further explore the mechanisms that link obesity and asthma in the pediatric population.